PELAKSANAAN KONSELING OBAT OLEH APOTEKER DI APOTEK KABUPATEN BADUNG - Anggreni, Ni Putu Ruscita (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 11 No 1 (2021): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2021.v11.i01.p02, 2021)
Republic of Indonesia Health Minister Regulation No. 73 of 2016 states that counseling is one of the pharmaceutical services at the Pharmacy. This study aims to determine the implementation of drug counseling by Pharmacists to patients in the Pharmacy in accordance with Republic of Indonesia Health Minister Regulation No. 73 of 2016. This type of research is non experimental with cross sectional design. In this study the data was taken using a questionnaire via Google Form . Fill out the google form by the pharmacists in Badung Regency. The data obtained were analyzed and then the percentage was made. Based on the data obtained, as many as 100% of respondents had counseled patients with varying time periods. Respondents had counseled within 1-10 minutes. When providing counseling, as many as 55.55% of respondents asked that there were those who needed help, such as lack of time, place and knowledge. Provision of information in the implementation of counseling, namely how to use and store drugs (100%), time of drug use (88.89%), drug dosage and duration of drug use (77.78%), and drug side effects (66.67%). This is good enough to increase patient approval for taking the drug. However, counseling documentation and recording patient documentation is still not effective in its implementation due to various factors. In terms of the pharmacist's knowledge regarding the laws governing the performance of pharmaceutical personnel, 88.89% of respondents already knew that. Therefore, it is expected that pharmacists can carry out their duties properly in accordance with statutory regulations.